Incoming Mail Archiving System Using the Waterfall at the Regional Secretary (SEKDA) of the Mayor's Office of Medan - Darmeli Nasution; Nasywa Rizki Fatihah; Muhammad Reendy Prayoga; Muhammad Sigit; Muhammad Naim Nasution (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Mail archive management is a crucial aspect of efficient administration, but it often requires a structured system to ensure data accessibility and accuracy. This journal discusses the use of Microsoft Excel as a tool for mail archiving, with a focus on the application of systematic and practical management methods. Excel, as a commonly used spreadsheet application, provides a variety of features that support the management of mail archives, including table creation, data sorting, and applying filters for quick searches. In this study, we outline the practical steps in composing a mail archive using Excel, from creating appropriate templates to filling in data and utilizing Excel functions for analysis. By using Excel, mail archive management can be done at a low cost and efficient process, allowing users to track and manage mail effectively. These findings are expected to provide practical guidance for organizations looking to utilize Microsoft Excel in their mail archive management systems.